Unusual Presentation of Hurthle Cell Carcinoma With TENIS Syndrome as Left Atrial Thrombus on 18F-FDG PET/CT. (October 2018) - Sood, Apurva; Parihar, Ashwin Singh; Sood, Ashwani; Kumar, Rajender; Prakash, Gaurav; Singhal, Manphool; Gulati, Ajay; Mittal, Bhagwant Rai; Bahl, Ajay; Singh, Shashank
Abstract : Abstract: Differentiated thyroid cancer (DTC) with thyroglobulin elevation and negative 131 I scintigraphy (TENIS) syndrome is a diagnostic and therapeutic dilemma. Treatment of differentiated thyroid cancer has an excellent outcome, but treatment options in TENIS are limited with the exception of surgically amenable disease. We present a case of TENIS syndrome with incidental detection of tumor thrombus in right pulmonary vein extending to the left atrium on 18 F-FDG PET/CT and subsequently complicating as an occipital bleed. The timely detection of the thrombus facilitated early initiation of anticoagulant therapy. However, the intracranial bleed precluded the continuation of anticoagulant therapy.